(untitled) (Boca Raton, 2014)
Featuring contributions from leading experts, the Road and Off-Road Vehicle System Dynamics Handbook provides comprehensive, authoritative coverage of all the major issues involved in road vehicle dynamic behavior. While the focus is on automobiles, this book also highlights motorcycles, heavy commercial vehicles, and off-road vehicles.
Keywords: Motor vehicles,Xe cơ giới; Dynamics,Động lực học